Digital economy and logistics as new areas of study in Higher Education - Nazarova lionella Nicolaevna, Kabanov Oleg Vladimirovich, Starostina Julia Evgenievna; Tsvetkova Izabella Ivanovna, Yakimova Tatiana Borisovna, Govorkov Aleksey Sergeevich; Ivanovich, Prasolov Valeriy (Opción, 2020)
The article discusses promising trends in the formation of the concept of creating an economy in the numerical sphere, reveals the difficulties that arise before the concept of creating a numerical community at the stage of development via comparative qualitative research methods. As a result, it is impossible to instill the principles of logistics if there is no rational distribution. In conclusion, Logistics provides an understanding not only of the logic of using the materials of this economic system, but also the knowledge gained about the state of the student’s knowledge.